2008
DOI: 10.1104/pp.108.126714
|View full text |Cite
|
Sign up to set email alerts
|

The ATG Autophagic Conjugation System in Maize: ATG Transcripts and Abundance of the ATG8-Lipid Adduct Are Regulated by Development and Nutrient Availability    

Abstract: Plants employ sophisticated mechanisms to recycle intracellular constituents needed for growth, development, and survival under nutrient-limiting conditions. Autophagy is one important route in which cytoplasm and organelles are sequestered in bulk into vesicles and subsequently delivered to the vacuole for breakdown by resident hydrolases. The formation and trafficking of autophagic vesicles are directed in part by associated conjugation cascades that couple the AUTOPHAGY-RELATED8 (ATG8) and ATG12 proteins to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
208
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 192 publications
(224 citation statements)
references
References 48 publications
(95 reference statements)
10
208
0
2
Order By: Relevance
“…S2). 32 We found more examples of identical ATG8 sequences in potato (StPGSC0003DMP400025414 with StPGSC0003DMP400038670) and soybean (Gm09g00630 with Gm15g11510). These results indicate that ATG4 and ATG8 genes are conserved among plant lineages.…”
Section: Identification Of Atg4s and Atg8s In The Plant Kingdommentioning
confidence: 99%
See 1 more Smart Citation
“…S2). 32 We found more examples of identical ATG8 sequences in potato (StPGSC0003DMP400025414 with StPGSC0003DMP400038670) and soybean (Gm09g00630 with Gm15g11510). These results indicate that ATG4 and ATG8 genes are conserved among plant lineages.…”
Section: Identification Of Atg4s and Atg8s In The Plant Kingdommentioning
confidence: 99%
“…30,31 However, little is known about ATG genes or autophagy mechanism in other plant species. Although a few ATG8 orthologs have been used as markers in some plants, [32][33][34][35][36][37] there is no systematic analysis of ATG4 and ATG8 in agronomically important crop plants.…”
Section: Introductionmentioning
confidence: 99%
“…As a control, we compared the expression pattern of ATG in cotyledons (see Supplemental Figure 5 online). We focused on genes encoding the ATG8 conjugation system because the expression of these genes is often regulated developmentally (van der Graaff et al, 2006;Chung et al, 2009). A preliminary search in the Genevestigator database (http://www.genevestigator.com) revealed that ATG3, ATG8b, ATG8g, and ATG8i showed higher expression levels in hypocotyls than in cotyledons.…”
Section: Expression Of Atg7 Is Induced In Hypocotyls But Not In Cotylmentioning
confidence: 99%
“…First, electron microscopic observation suggested pexophagy in castor bean (Ricinus communis) endosperm (Vigil, 1970), although similar observations have not been reported. Second, Atg genes encoding core autophagic machineries are highly conserved in various eukaryotes, including dicots (Hanaoka et al, 2002;Doelling et al, 2002) and monocots (Chung et al, 2009), and reverse genetic studies using Arabidopsis demonstrated their functions in plant autophagy (reviewed by Kim et al, 2012). Of four conserved core autophagic complexes, the ATG8 conjugation system has been the most extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…Two putative ATG13 genes were found in Arabidopsis, but their similarity is restricted to a relatively small region of the protein and it is currently unclear if they are true ATG13 orthologs (Bassham et al, 2006). Recently, rice and maize ATG genes have also been identified and have been characterized (Su et al, 2006;Chung et al, 2009;Xia et al, 2011).…”
Section: Autophagy Mechanism In Plants Core Machinery Of Autophagy Ismentioning
confidence: 99%